Sử dụng một số phương pháp dạy học tích cực trong dạy học phân môn Lịch sử 4 góp phần nâng cao chất lượng và hiệu quả dạy học ở trường tiểu học - Lê, Thúy Mai; Nguyễn, Minh Thảo; Nguyễn, Tùng Lâm; Nguyễn, Thị Mai Linh (Tạp chí Giáo dục, 2024)
In the present educational trend, in addition to shifting from content-based education to learner competence-based education, teaching methods are constantly evolving to ensure innovation and boost the efficiency of student learning. Teachers in primary schools must have a fundamental knowledge of active teaching approaches to use and integrate them into the teaching process and pique students’ interest. This article mentions the use of some active teaching methods that contribute to improving the effectiveness of teaching the 4th grade History program, thereby improving the quality of teaching History program at primary schools. The application of different active teaching approaches for Grade 4 History subject (“Kết nối tri thức với cuộc sống” book series) is mentioned in the article in order to assist teachers in improving their teaching effectiveness.